Proposal of FCbT Considering Closed‐Loop Stability at Each Parameter Update. Issue 1 (January 2015) - Yubai, Kazuhiro; Fujii, Hiroki; Hirai, Junji
SUMMARY We propose a controller tuning method that considers closed‐loop stability after controller tuning without a mathematical plant model. We propose fictitious correlation‐based tuning that yields reasonable controller parameters using a small amount of input and output data. However, closed‐loop stability after controller tuning is not guaranteed in this approach. In this investigation, we impose a stability constraint on the parameter update in order to maintain closed‐loop stability at each parameter update. Further, by introducing particle swarm optimization instead of the Gauss–Newton method to solve the constrained nonlinear optimization problem, the initial value dependence is considerably reduced. The effectiveness of the proposed method is confirmed by a numerical example and experimental results.